Analysis of Variety of Learning Difficulties in Indonesian Language Education Students on English Language Courses at University of Ma'arif Nu Kebumen - Alek Andika; Endah Mitsalina (ETERNAL (English Teaching Journal), 2020)
Mastery of English as an international language is a necessity at this time. Indonesia as a member of the AEC (ASEAN Economic Community) should properly prepare for this challenge by preparing a capable and skilled generation of the nation. English is an international language that is very important for communication and connecting people with the world in various aspects including education. The government shows its seriousness in improving English language skills to the nation's generation, namely by requiring English at the educational level. In reality, there are various difficulties faced by students when learning English, especially in learners / students who are not from the English department called ESP (English for Specific Purposes) Learners. This study aims to explore deeper into the variety of difficulties faced by students in learning English in students of Indonesian Language Education Study Program at FKIP University of Ma'arif NU Kebumen. This study uses a qualitative approach with questionnaire instruments, observation and in-depth interview. Analysis of research data was carried out through three stages, namely data reduction, data presentation and conclusion drawing. The results of this study indicate that research subjects face a variety of difficulties learning English, namely: 1) lack of student confidence, 2) students rarely use English in daily life and, 3) lack of vocabulary mastery.